Overview Of Theology And Science Against Water Baptism Virtually By Virtual Reality Church - Rinto Francius Sirait; Herdi Rondang Ulina Pardede; Gabriel Sianipar (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
One of the churches that performs services by utilizing the development of information technology is the virtual reality church pastored by DJ Soto. All services are carried out virtually. In its service information, this church offers water baptism sacrament services which are carried out virtually. This research aims to conduct a theological and scientific study of virtual water baptism so that it becomes input for believers and God's church. This study used a descriptive qualitative approach, in which the primary data was obtained by means of literature review. The results of the study show that water baptism carried out by the virtual reality church has no biblical basis, so believers and God's church must reject this baptism.